HUBUNGAN ADVERSITY QUOTIENT DENGAN TINGKAT STRES PADA MAHASISWA TAHUN PERTAMA FAKULTAS KEDOKTERAN UNIVERSITAS RIAUMedical - Sari, Charmila; ", Firdaus; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Medical students, especially fresh students are vulnerable to get stress. Thestress level on each student is influenced by many factors, one of the factors isAdversity Quotient. A nice AQ is able to help somebody to face the stress. Thepurpose of this research is to discover the relationship between Adversity Quotientand the stress level on fresh student in Medical Faculty of Riau University. Researchdesign used in this research is analytic correlative and cross sectional approach.Total samples are 110 people, sampling technique is Total Sampling. Collecting dataused Adversity Quotient questionnaire based on theory of Paul G Stoltz and MedicalStudent Stressor Questionnaire (MSSQ). The result of research showed that 6 people(5.5%) who has mild stress level, 76 people (69,1%) who has medium stress level, 28people (25,5%) who has heavy stress level, and no one who are severe stress level.Analyzing data used Spearman correlation test and significance level p < 0,05, it isacquired that rate p = 0,00, rate r = -0,504 and rate r Square = 0,254. It means thereis significant negative connection on fresh student in Medical Faculty of RiauUniversity.Keyword: stress level, adversity quotient